2003
DOI: 10.1046/j.1365-2036.2003.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of unlicensed and off‐label medications in paediatric gastroenterology with a review of the commonly used formularies in the UK

Abstract: SUMMARYBackground: Use of unlicensed and off-label medications is common in hospital based paediatric practice. Whilst inpatient prescription can be closely monitored within the hospital setting, it is subspecialties like paediatric gastroenterology, caring for chronically ill children on an outpatient basis that require administration of regular medications in the community. Local practitioners rely on available paediatric formularies or information provided by the tertiary unit for monitoring and dispensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 5 publications
2
25
1
3
Order By: Relevance
“…Several researchers investigated the relationship between off-label and unlicensed drug uses and recommendations from evidence-based drug therapy sources [25,34,43,58,72,73,80] and found that they generally correspond, indicating that the quality of drug therapies is not necessarily related to drug license status.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers investigated the relationship between off-label and unlicensed drug uses and recommendations from evidence-based drug therapy sources [25,34,43,58,72,73,80] and found that they generally correspond, indicating that the quality of drug therapies is not necessarily related to drug license status.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the submitted data focused on hospitalised children and off-label drug use within various age sub-groups. Some of them were performed at specialised wards as paediatric gastroenterology or neonatal intensive care unit [12,13]. Most of the results confirm widespread off-label and unlicensed use of drugs in Europe, which refers to 45-60% of all administered medicinal products to paediatric population.…”
Section: Current Situation Among European Countriesmentioning
confidence: 84%
“…Os 20 trabalhos incluídos na análise foram realizados em 10 diferentes países, sendo 14 países europeus, Brasil (2), EUA (1), Nova Zelândia (1) e Israel (2). Dos estudos, 13 foram desenvolvidos em hospitais, dois em atenção primaria e três em outros contextos [1][2][3][4]9,10,[25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Resultsunclassified
“…A prescrição de medicamentos não-licenciados ou de uso não-padronizado em crianças é uma realidade condicionada por fatores tais como ausência de produtos licenciados para pacientes pediátricos, carência de apresentações farmacológicas de uso mais flexível e prevalência elevada de medicamentos comercializados sem informação sobre a dose para crianças [1][2][3][4] . Tais dificuldades tornam o uso de medicamentos em crianças menos seguro e com resultados menos previsíveis e confiáveis do que aquele que ocorre em adultos.…”
Section: Introductionunclassified